Industrialization, Productivity and the Shift to Services and Information. Issue 11 (22nd May 2015) - Karmarkar, Uday S.; Kim, Kihoon; Rhim, Hosun
Abstract : All major world economies are exhibiting a shift from products to services in terms of relative share of GNP and employment. A well accepted explanation for this shift to services has been the lower productivity growth in services relative to manufacturing. A second trend visible in the United States and other advanced economies is that from material‐intensive to information‐intensive sectors with the latter growing relative to the former. There does not seem to be a generally accepted explanation for this shift; in fact, here it would appear that productivity in information‐intensive sectors is increasing. We construct a model of an economy with endogenous production and consumption decisions by utility maximizing individuals. We show that differential productivity changes can result in either relative growth or decline of a sector. A second factor affecting the direction of change is the degree to which consumption of sector outputs approaches satiation. When marginal utility of additional consumption drops sufficiently low, productivity increases can lead to declines in the relative size and share of, and employment in the sector. Concurrently, increases in productivity increase average wealth as expected, but income inequality can either increase or decrease.